Analgesic and anti-inflammatory effects of oral Centella asiatica (L.) urban extract in cats undergoing ovariohysterectomy - Xiao Yi; Areerath Akatvipat; Nicha Mongkolrat; Phitchaya Saenubol; Pachara Pornnimitara; Sukolrat Boonyayatra (Elsevier, 2023)
Background: Centella asiatica Linn Urban (CA) is a medicinal herb used in traditional medicine for its anti-inflammatory and antinociceptive properties. Feline species usually exhibit toxicity toward nonsteroidal anti-inflammatory drugs, and thus the analgesic potential of CA is worth investigating in domestic cats. Purpose: The objective of this study was to evaluate the efficacy of CA extract in oral formulation for controlling postoperative pain and inflammation in cats undergoing ovariohysterectomy. Study Design: Randomized, prospective, blind, placebo-controlled study. Methods: This study included 18 healthy female cats randomized into three groups: control, low-dose group (100 mg/kg), and high-dose group (200 mg/kg). Accordingly, subjects were given orally administered placebo jelly or CA mixed jelly 12 h before surgery and 4, 24, 48, and 72 h after surgery. Serum amyloid A (SAA) and white blood cell count (WBC) were tested 23 h after surgery. Postoperative pain was evaluated at 4, 8, 24, 48, and 72 h after extubation by using the UNESP-Botucatu multidimensional composite pain scale (UFEPS). Wound scores were assessed using an infrared thermal imaging camera and normal pictures token at right after the surgery and at 1, 2, and 3 days after the surgery. SAA and WBC values were compared between groups via ANOVA (p < 0.05). The Scheirer-Ray-Hare test was used to analyze the ordinal score: pain score and wound-healing score (p < 0.05). Results: The high-dose group had a significantly lower UFEPS score than the control group (p = 0.007). In the high-dose group, few cats had a high temperature at the surgical wound after surgery. The level of SAA, WBC, and wound scores showed no significant difference among groups. No adverse side effects were found after receiving the CA extract. Conclusion: CA extract powder can be used as an analgesic in domestic cats for preventing and treating postoperative pain. The dosage and frequency of CA oral administration should be further studied.